The challenges faced by service providers on satellite mental health-care facilities in Yangon, Myanmar: a qualitative study - Kyaw Lin; Sun Lin; Than Tun Sein (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - Myanmar has an insufficient number of mental health workers with few institutional facilities resulting in a significant treatment gap. Although few mental health services are integrated into primary health care (PHC), the challenges are unknown. This study aimed to assess the challenges perceived by providers in the service delivery of satellite mental health care (SMHC) in two sample townships in Yangon. Design/methodology/approach - The research was based on a case study design by applying a qualitative approach using in-depth interviews (IDIs). In the three types of service providers, a total of six staff participated as interviewees. These consisted of two team leaders, two clinical specialists providing consultations to clients and two mental health nurses. Findings - Providers perceived the following as major challenges in the provision of services: unstable financial resources and management, insufficient human resources and capacity of service providers, restricted outpatient services, the lack of a functional referral system, overcrowding, inadequate individual consultation time, long-waiting hours, finite opening days and hours and poor setting of infrastructure, resulting in lack of privacy. Research limitations/implications - In the absence of similar studies in Myanmar, findings could not be placed in the context of the national literature for comparison. Further, the study involved a limited number of respondents, which may have affected the findings. Originality/value - Although the challenges revealed were not uncommon in mental health services in developing countries, this study focused on a specific model of mental health care integrated into general healthcare settings in Myanmar. The findings offer a benchmark on efforts to develop decentralized mental health services in Myanmar and provide input for future in-depth studies.